let v1, v2 be Element of V; :: thesis: ( ex F being FinSequence of V st
( F is one-to-one & rng F = Carrier L & v1 = Sum (L (#) F) ) & ex F being FinSequence of V st
( F is one-to-one & rng F = Carrier L & v2 = Sum (L (#) F) ) implies v1 = v2 )

given F1 being FinSequence of the carrier of V such that A3: F1 is one-to-one and
A4: rng F1 = Carrier L and
A5: v1 = Sum (L (#) F1) ; :: thesis: ( for F being FinSequence of V holds
( not F is one-to-one or not rng F = Carrier L or not v2 = Sum (L (#) F) ) or v1 = v2 )

given F2 being FinSequence of the carrier of V such that A6: F2 is one-to-one and
A7: rng F2 = Carrier L and
A8: v2 = Sum (L (#) F2) ; :: thesis: v1 = v2
defpred S1[ object , object ] means {\$2} = F1 " {(F2 . \$1)};
A9: dom F2 = Seg (len F2) by FINSEQ_1:def 3;
A10: dom F1 = Seg (len F1) by FINSEQ_1:def 3;
A11: len F1 = len F2 by ;
A12: for x being object st x in dom F1 holds
ex y being object st
( y in dom F1 & S1[x,y] )
proof
let x be object ; :: thesis: ( x in dom F1 implies ex y being object st
( y in dom F1 & S1[x,y] ) )

assume x in dom F1 ; :: thesis: ex y being object st
( y in dom F1 & S1[x,y] )

then F2 . x in rng F1 by ;
then consider y being object such that
A13: F1 " {(F2 . x)} = {y} by ;
take y ; :: thesis: ( y in dom F1 & S1[x,y] )
y in F1 " {(F2 . x)} by ;
hence y in dom F1 by FUNCT_1:def 7; :: thesis: S1[x,y]
thus S1[x,y] by A13; :: thesis: verum
end;
consider f being Function of (dom F1),(dom F1) such that
A14: for x being object st x in dom F1 holds
S1[x,f . x] from A15: f is one-to-one
proof
let y1, y2 be object ; :: according to FUNCT_1:def 4 :: thesis: ( not y1 in dom f or not y2 in dom f or not f . y1 = f . y2 or y1 = y2 )
assume that
A16: y1 in dom f and
A17: y2 in dom f and
A18: f . y1 = f . y2 ; :: thesis: y1 = y2
F2 . y1 in rng F1 by ;
then A19: {(F2 . y1)} c= rng F1 by ZFMISC_1:31;
F2 . y2 in rng F1 by ;
then A20: {(F2 . y2)} c= rng F1 by ZFMISC_1:31;
( F1 " {(F2 . y1)} = {(f . y1)} & F1 " {(F2 . y2)} = {(f . y2)} ) by ;
then {(F2 . y1)} = {(F2 . y2)} by ;
then F2 . y1 = F2 . y2 by ZFMISC_1:3;
hence y1 = y2 by A6, A11, A10, A9, A16, A17; :: thesis: verum
end;
set G1 = L (#) F1;
A21: len (L (#) F1) = len F1 by Def7;
A22: rng f = dom F1
proof
thus rng f c= dom F1 ; :: according to XBOOLE_0:def 10 :: thesis: dom F1 c= rng f
let y be object ; :: according to TARSKI:def 3 :: thesis: ( not y in dom F1 or y in rng f )
assume A23: y in dom F1 ; :: thesis: y in rng f
then F1 . y in rng F2 by ;
then consider x being object such that
A24: x in dom F2 and
A25: F2 . x = F1 . y by FUNCT_1:def 3;
F1 " {(F2 . x)} = F1 " (Im (F1,y)) by ;
then F1 " {(F2 . x)} c= {y} by ;
then {(f . x)} c= {y} by A11, A10, A9, A14, A24;
then A26: f . x = y by ZFMISC_1:18;
x in dom f by ;
hence y in rng f by ; :: thesis: verum
end;
then reconsider f = f as Permutation of (dom F1) by ;
( dom F1 = Seg (len F1) & dom (L (#) F1) = Seg (len (L (#) F1)) ) by FINSEQ_1:def 3;
then reconsider f = f as Permutation of (dom (L (#) F1)) by A21;
set G2 = L (#) F2;
A27: dom (L (#) F2) = Seg (len (L (#) F2)) by FINSEQ_1:def 3;
A28: len (L (#) F2) = len F2 by Def7;
A29: dom (L (#) F1) = Seg (len (L (#) F1)) by FINSEQ_1:def 3;
now :: thesis: for i being Nat st i in dom (L (#) F2) holds
(L (#) F2) . i = (L (#) F1) . (f . i)
let i be Nat; :: thesis: ( i in dom (L (#) F2) implies (L (#) F2) . i = (L (#) F1) . (f . i) )
assume A30: i in dom (L (#) F2) ; :: thesis: (L (#) F2) . i = (L (#) F1) . (f . i)
then reconsider u = F2 . i as VECTOR of V by ;
A31: ( (L (#) F2) . i = (L . (F2 /. i)) * (F2 /. i) & F2 . i = F2 /. i ) by ;
i in dom f by ;
then A32: f . i in dom F1 by ;
then reconsider m = f . i as Element of NAT ;
reconsider v = F1 . m as VECTOR of V by ;
{(F1 . (f . i))} = Im (F1,(f . i)) by
.= F1 .: (F1 " {(F2 . i)}) by A11, A28, A10, A27, A14, A30 ;
then A33: u = v by ;
F1 . m = F1 /. m by ;
hence (L (#) F2) . i = (L (#) F1) . (f . i) by A21, A10, A29, A32, A33, A31, Def7; :: thesis: verum
end;
hence v1 = v2 by A3, A4, A5, A6, A7, A8, A21, A28, Th6, FINSEQ_1:48; :: thesis: verum